Oxford Advanced Learner's Dictionary - International Students Edition - Hornby, A.S. (Oxford, United Kingdom Oxford University Press, 1995)
The Oxford Advanced Learner$1 (Bs Dictionary is a trusted resource for students learning English as a second language. It provides over 100,000 words, phrases, and meanings with clear explanations and real-life usage examples. Special features include collocations, synonyms, writing tips, and pronunciation guides to enhance fluency and understanding. This edition supports learners preparing for academic exams such as IELTS and TOEFL.s
Includes comprehensive definitions, usage notes, and example sentences designed for intermediate to advanced English learners. This edition may include a CD-ROM with interactive practice tools.
Keywords: Oxford Advanced Learner$1 (Bs Dictionarys